Supervisory Competence of School Heads and Teachers’ Dedication in Mati South District, Mati City - Bandera, Maricor D. (PPSDP International Journal of Education, 2024)
This study aimed to explore the influence of supervisory competence of school heads on the teachers’ dedication. In this study, the researcher selected the 190 elementray school teachers in Mati South District, Mati City as the respondents of the study. Stratified random sampling technique was utilized in the selection of the respondents. Non-experimental quantitative research design using descriptive correlational method was employed. The data collected were subjected on the following statistical tools: Mean, Pearson Moment Product Correlation and regression analysis. Findings revealed that supervisory competence of school heads was rated as extensive, while, teachers’ dedication in Mati South District, Mati City was described as moderately extensive. Further, correlation analysis demonstrated that there is a significant relationship between supervisory competence of school heads and teachers’ dedication in Mati South District, Mati City. Evidently, regression analysis proved that supervisory competence of school heads in terms of curriculum and assessment; and teacher development and support were significant predictors of teachers’ dedication in Mati South District, Mati City.